Six years' experience with the discontinuation of BCG vaccination. 2. Cost and benefit of mass BCG vaccination - Trnka, L; Danková, D; Svandová, E (Tubercle and lung disease, 1993)
In 1986 the compulsory mass BCG vaccination of infants born in a selected area of the Czech Republic was abolished. The observed annual risk of tuberculous infection in children aged 0-6 years was below 0.1% and the annual risk of tuberculous disease 7/100,000. The increase of tuberculous cases among nonvaccinated children indicated a protective efficacy of BCG vaccine of 80%. A benefit analysis proved that the advantages and disadvantages of BCG vaccination were in balance. The number of nonvaccinated children developing tuberculosis was so small that mass application of BCG has been found to be redundant. The important advantage of not using the vaccination is the maintenance of the epidemiological and diagnostic value of tuberculin tests. The tests in connection with preventive chemotherapy remain an important tool, enabling control of infected individuals.
Keywords: Vaccination; Czechoslovakia; Infant; incidence; Male; Mycobacterium Infections; lidé; Tuberculosis; Humans; Child; Cost-Benefit Analysis; Incidence; novorozenec; Child, Preschool; mykobakteriózy; BCG Vaccine; mužské pohlaví; kojenec; tuberkulóza; dítě; ženské pohlaví; Female; Československo; analýza nákladů a výnosů; vakcinace; Infant, Newborn; předškolní dítě; BCG vakcína